On linear homogeneous almost periodic systems that satisfy the Favard condition - Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove the existence of a linear homogeneous almost periodic system of differential equations that has nontrivial bounded solutions and is such that all systems from a certain neighborhood of it have no nontrivial almost periodic solutions.